Effects of Silver Nanoparticle Modified Corchorus olitorius (Jute) Leaf Extract on Blood Sugar and Lipid Profile of Diabetic Wistar Rats (African Journal of Biomedical Research, 2024)
Diabetes, a high prevalent and non-infectious disease characterized with expensive management coupled with its complication exerts serious economic burden on patients and healthcare practitioners. This study aimed at evaluating the effects of silver nanoparticles modified Corchorus olitorius leaf extracts (AgNPs-COLE) on blood sugar and lipid profile of alloxan induced diabetic wistar rats. Phytochemical screening of Corchorus olitorius leaf extract (COLE) was carried out using gravimetric method. The energy dispersive x-ray fluorescence spectrometer was used to determine the elemental content of green synthesized silver nanoparticles. Thirty five (35) Wistar rats of 184 – 201g were used and grouped into A-G of 5 per group. Group A were non-induced and not treated except feeding only, Groups B-G were induced with diabetes using 130mg/kg alloxan monohydrate, while Group B were not treated, group C were administered 10mg/kg glibenclamide (GLB), groups D and E were administered with aqueous leaf extracts of Cochorus olitorius of 200mg/kg and 400mg/kg, respectively, and groups F and G were administered with 200 mg/kg and 400mg/kg of AgNPs modified Jute leaf extract, respectively. The blood sugar level and lipids assay were determined. Data analysis was carried out using multivariate ANOVA of SPSS version 26 with inferior p-value of 0.05. Alkaloid, flavonoid, terpernoids, steroid and saponins were predominant phytochemicals with yields of 16.46, 11.42, 6.9, 3.58 and 2.42 %. Blood sugar levels of the rats were significantly reduced in all groups following treatment regime. Total cholesterol, TG, HDL-C and LDL-C levels of diabetic rats significantly reduced when administered with AgNPs-COLE compared to COLE and GLB, respectively. Thus, silver nanoparticles enhanced anti-diabetogenic potentials of C. olitorius leaf extract and performed better than glibenclamide in diabetes management.